2012
DOI: 10.1111/j.1460-9592.2012.03810.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal administration with dexmedetomidine does not impair the rat hippocampal synaptic plasticity later in adulthood

Abstract: These findings demonstrate that a single administration of DEX to rats on P7 preserves hippocampal synaptic plasticity as well as synaptic transmission later in life. In view of the some evidence that have demonstrated the permanent detrimental impact of commonly used anesthetics on neurological outcomes after neonatal exposure, our findings may suggest the relative safety of DEX administered as a sedative agent to neonatal animals with regard to the development of hippocampal synaptic functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
(53 reference statements)
0
27
0
Order By: Relevance
“…The present study does not further characterize dexmedetomidine nor does it provide evidence that dexmedetomidine causes respiratory suppression because the animals received no other sedatives and because dexmedetomidine was administered at a dose higher than that used to achieve sedative effects in neonatal rats . Nonetheless, the present findings do indicate the functional effects of the α 2 ‐adrenoceptor on respiratory control in newborn rats.…”
Section: Discussionmentioning
confidence: 63%
“…The present study does not further characterize dexmedetomidine nor does it provide evidence that dexmedetomidine causes respiratory suppression because the animals received no other sedatives and because dexmedetomidine was administered at a dose higher than that used to achieve sedative effects in neonatal rats . Nonetheless, the present findings do indicate the functional effects of the α 2 ‐adrenoceptor on respiratory control in newborn rats.…”
Section: Discussionmentioning
confidence: 63%
“…This test is used in rodents for assessing spatial learning and memory. Three of these studies examined whether administration of dexmedetomidine alone causes impaired outcome . These studies showed that the outcome of the tests is worse after exposure to anesthetics compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…The same holds true for future application of principles of pharmacovigilance studies. This is especially of interest since experimental studies have suggested that dexmedetomidine may have neuroprotective effects as well …”
Section: Discussionmentioning
confidence: 99%
“…This is especially of interest since experimental studies have suggested that dexmedetomidine may have neuroprotective effects as well. 106,107…”
Section: Discussionmentioning
confidence: 99%